Capillary evaporation of water from aluminum high-temperature conductive microporous coating. (June 2020) - Wang, Xiaomeng; Fadda, Dani; Godinez, Juan C.; Lee, Jungho; You, Seung M.
Highlights: Wicking in Aluminum high temperature conductive microporous coating (Al-HTCMC). Effects of microporous coating on wicking and evaporation performance. Evaluation procedure of upward wicking at different operating conditions. Experimentally validated analytical prediction of the dryout heat flux. Identification of a characteristic parameter to classify large coated surfaces. Abstract: Effective heat dissipation of a persistent surface heat flux is eagerly demanded in a multitude of applications. Such heat dissipation can be accomplished with thin-film evaporation, where metallic wicking structures are developed to effectively spread liquid over a surface to keep it wet during the heat transfer process. Capillary forces, permeability, and wicking thickness are the main properties that determine thin-film spreading and, thus, the evaporation performance. To achieve effective wicking, an aluminum High-Temperature Conductive Microporous Coating (Al-HTCMC) is used. The coating consists of aluminum particles that are brazed onto an aluminum surface. The coating, with different average particle diameters (dp = 11, 24, 66 and 114 µm), is applied over the aluminum plate (50.8 mm × 152.4 mm × 3.3 mm). Distilled water is selected as the working fluid and rate of rise experiments are performed to determine the effective meniscus radius and the permeability of unheated Al-HTCMC surfaces. Evaporation experiments at saturated conditions reveal that nearly zero superheat is needed for evaporation along a large vertical heater with area of 50.8 × 127 mm 2 . The temperature across the entire surface remains uniform until the dryout heat flux occurs, regardless of particle size at heat flux values up to 1.49 W/cm 2 over the entire heater's area. A theoretical model is used to predict the dryout heat flux based on pressure drop through the microporous layer. Experimental results are in good agreement with the prediction model.